Signaling vision: Knowing when to quit - Junichiro Ishida; Wing-chuen Suen (Osaka University, Institute of Social and Economic Research (ISER), 2024)
We study a signaling game where agents signal their type by choosing when to quit pursuing an uncertain project. High types observe news about project quality and quit when bad news arrives. This creates opportunities for low types who do not observe any news to mimic high types by quitting strategically. In equilibrium, there is a mimicking phase of time when low types quit continuously. The reputation dynamics may exhibit non-monotonicity, with agents who quit either very early or very late carrying a higher reputation than do agents who quit near the optimal time for low types. Our analysis offers a unifying explanation for how and when both early and late quitting can enhance reputation and suggests novel welfare and policy implications.
Keywords: D82; O31; 330; perseverance; behavioral diversity; mimicking; non-monotone reputation dynamics; bandit experimentation